Bioinformatics with computational biology- A synergistic effect - MARGI GANDHI,; RAJASHREE MASHRU, (International Journal of Pharma and Bio Sciences, 2019)
Nowadays Bioinformatics and computational biology has emerged as an interdisciplinary field that develops and applies computational methods to analyse large collections of biological data. Earlier bioinformatics term had different meaning, it referred to the study of information processes in biotic systems like biochemistry and biophysics. However with the emergence of bioinformatics tools it lead to the development of protein sequencing methods from a variety of organisms and with the availability of protein sequences it helped in determining sequences of insulin. The major challenge to bioinformatics tools was to manually handle large number of protein sequences of different organisms. Thus to overcome this limitation new computer methods were developed. The objective of the current review article is to addresses the limitations of bioinformatics field and how these limitations were overcome when computational biology was combined with bioinformatics. This article also includes recent application highlighting synergistic effect of bioinformatics with computational biology in various fields like drug discovery and development, food, treatment of neglected tropical diseases like TB, HIV, Leishmaniasis and malaria, Inï¬‚uenza surveillance and vaccine strain selection and development of precision medicine.